2023
DOI: 10.4266/acc.2022.01116
|View full text |Cite
|
Sign up to set email alerts
|

Study of the gut microbiome as a novel target for prevention of hospital-associated infections in intensive care unit patients

Abstract: Background: Hospital-acquired infections (HAIs) are increasing due to the spread of multi-drug-resistant organisms. Gut dysbiosis in intensive care unit (ICU) patients at admission showed an altered abundance of some bacterial genera associated with the occurrence of HAIs and mortality. In the present study, we investigated the pattern of the gut microbiome in ICU patients at admission to correlate it with the development of HAIs during ICU stay. Methods: Twenty patients admitted to the ICU were included in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…3 b, c). Loss of gut microbiome diversity in the critically ill is linked with depletion of short-chain fatty acid biosynthesis, conferring an increased risk of developing hospital-acquired infections [ 4 , 5 , 44 ]. Patients who received anaerobic antibiotic coverage in the ICU had increased concentration of Enterococci in their stool, which translated into higher numbers of organ failures and mortality rates [ 13 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…3 b, c). Loss of gut microbiome diversity in the critically ill is linked with depletion of short-chain fatty acid biosynthesis, conferring an increased risk of developing hospital-acquired infections [ 4 , 5 , 44 ]. Patients who received anaerobic antibiotic coverage in the ICU had increased concentration of Enterococci in their stool, which translated into higher numbers of organ failures and mortality rates [ 13 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…In an interesting study in hospitalized humans, it was observed that microbiota-derived lantibiotics similar to nisin could reverse resistance in vancomycin-resistant Enterococcus faecium, a leading cause of hospital infection [96]. Consuming live microorganisms such as Lactobacillus lactis, able to produce nisin A, decreased infections and mortality in intensive care units [97,98]. The pore-forming ability of nisin was shown to depend on the lipid microenvironment, with the lipid cardiolipin facilitating pore formation in mitochondria, possibly leading to cell death and applications against cancer; small natural molecules, phloretin and capsaicin, were also found to potentiate the membrane activity of nisin [99].…”
Section: Chemical Structure and Mode Of Action For Ampsmentioning
confidence: 99%